Adenosine A2A receptor availability in cerebral gray and white matter of patients with Parkinson's disease - Waggan Imran; Rissanen Eero; Tuisku Jouni; Matilainen Markus; Parkkola Riitta; Rinne Juha O; Airas Laura (United Kingdom, 2025)
Objective: Atrophic changes in cerebral gray matter of patients with PD have been reported extensively. There is evidence suggesting an association between cortical gyrification changes and white matter abnormalities. Adenosine A2A receptors have been shown to be upregulated in cerebral white matter and on reactive astrocytes in preclinical models of neurodegenerative diseases. We, therefore, sought to investigate in vivo changes in A2A receptor availability in cerebral gray and white matter of PD patients and its association with gray matter atrophy.
Methods: Eighteen patients with PD without dyskinesia and seven healthy controls were enrolled for this study. Brain MRI and dynamic PET scan was acquired with [11C]TMSX radioligand which binds selectively to A2A receptors. FreeSurfer software was used to segment cerebral gray and white matter structures. The resulting masks were used to calculate region specific volumes and to derive distribution volume ratios (DVRs), after co-registration with PET images, for the quantification of specific [11C]TMSX binding.
Results: We showed an increase in A2A receptor availability in frontal (P < 0.001) and parietal (P < 0.001) white matter and a decrease in occipital (P = 0.02) gray matter of PD patients as compared to healthy controls. A decrease in gray matter volume ratios was observed in frontal (P < 0.01), parietal (P < 0.001), temporal (P < 0.01) and occipital (P < 0.01) ROIs in patients with PD versus healthy controls.
Conclusions: Our results suggest a role of A2A receptor-based signaling in the neurodegenerative changes seen in the cerebral gray and white matter of patients with PD.